Effect of salt coatings on low cycle fatigue behavior of nickel-base superalloy GTM-SU-718 - Mahobia G.S.; Sudhakar R.G.; Antony A.; Chattopadhyay K.; Santhi Srinivas N.C.; Singh V. (My University, 2025)
Nickel-base superalloys are used as components of gas turbines both of jet engines as well as marine engines. Since these components are subjected to high temperature and oxidizing environment, their performance is drastically affected by the environmental conditions. Marine environment further aggravates the situation due to presence of salt (NaCl) particles in air. This salt along with sulphur and vanadium present in the fuel oil, leads to formation of compounds like sodium sulfate (Na2SO4) and vanadium pentaoxide (V2O5) during combustion and causes hot corrosion and stress corrosion cracking of engine components. Strain controlled low cycle fatigue tests were conducted on the nickel base superalloy GTM-SU-718 in air, at room temperature on unexposed, exposed at 550°C for 25h, exposed at 650°C for 25 h as well as on the specimens coated with layers of NaCl, 25wt.%NaCl+75wt.%Na2SO4 and 90wt.%Na2SO 4+5wt.%NaCl+5wt.%V2O5 salt/salt mixtures separately and exposed at elevated temperatures for 25 h. While the NaCl coated sample was exposed at 550°C, those coated with other two salt mixtures were exposed at 650°C. It was observed that fatigue life of the NaCl coated sample, exposed at 550°C for 25 h was reduced, however, there was little effect on fatigue life of the other specimens referred to above, including even those coated with salt mixtures and exposed at 650°C. © 2013 The Authors.